Design of Continuous Mode Hybrid Standalone Power Station with Hybrid Controller to Select the Best Optimal Power Flow - Dwivedi, Arpan; Pahariya, Yogesh (International Journal of Computer Sciences and Engineering, 2025)
In this paper design of continuous mode Hybrid Stand alone power station with battery and Diesel generator is modelled. The controller is designed to maximize the usage of energy sources and reduces the use of diesel generator. The state of battery charging is maintained. This paper firstly focuses on design of hybrid power station is to full fill load demand. Secondly a relay based controller is designed to select the best optimal power output as per availability of sources to minimize the use of Diesel generator and Battery operation. A supervisor control modes are further discussed for hybrid controller as per the load demand.